Copper oxide nanoparticles from Rabdosia rubescens attenuates the complete Freund’s adjuvant (CFA) induced rheumatoid arthritis in rats via suppressing the inflammatory proteins COX-2/PGE2 - Zhongbo Zhang (Arabian Journal of Chemistry, 2020)
Rheumatoid arthritis is a common auto-immune disease that affects nearly 1% of the total population worldwide and primarily occurs in the age group of 30–50. The copper oxide nanoparticles (CuONPs) were gained extensive research interests due to their immense biological benefits. This investigation was aimed to synthesize the CuONPs from R. rubescens leaves and examining its anti-arthritic potential against CFA-stimulated arthritis in rats. The formulated CuONPs from R. rubescens was characterized by UV–vis spectroscopy, TEM, XRD, and FT-IR. Arthritis was induced to animals by injecting 0.1 ml of CFA via an intra-planter route. Bodyweight and arthritis score was measured and tabulated and inflammatory markers i.e. IL-10, IL-6, TNF-α, IL-1β, Cox-2 and PGE2 in the serum was examined via ELISA kits. The status of TBARS, antioxidant enzymes, and liver marker enzymes were examined via standard procedures. The hind limb histology was examined microscopically by H&E staining. The UV–vis, XRD, and TEM studies were proved the existence of metallic RR-CuONPs. The RR-CuONPs treated arthritic animals displayed the enhanced bodyweight, reduced paw volume, and arthritic score. RR-CuONPs treatment also improved the antioxidant enzymes and diminished the pro-inflammatory markers. Histopathological investigation proved that the RR-CuONPs were suppressed the bone joints by preventing the inflammatory cell penetration and bone damage. The findings of this investigation were evidenced by the anti-inflammatory and anti-arthritic potentials of fabricated RR-CuONPs against CFA-stimulated arthritis in rats.